The limits of devolving sustainable development to the local level: The case of the Greenbelt of Fennoscandia initiative - Florin, Ian (Sociologia Ruralis, 2023)
This article investigates how the framing of nature conservation in terms of sustainable development both enables and constrains participation at the grassroots level. The Green Belt of Fennoscandia, an initiative to develop a transnational ecological network between Finland, Russia and Norway, is used as a case study. A desk study and 40 interviews with participants of two regional working groups from this initiative show how the mobilisation of the concept of sustainability encourages actors in rural areas to become leaders of projects in favour of both nature conservation and economic development. This research also describes how the lack of state engagement and potential conflicts between regional and national levels can discourage these actors to commit to the initiative. This research refines previous work on the reduction of the role of the state in conservation, illustrating the scalar dynamics of sustainable development implementation in a European rural context. It provides material to inform the governance of large-scale conservation projects, by highlighting how an approach that aims to boost local participation can in fact discourage it, if the reduction of the role of the state is not accompanied by resources, formal rights to democratic representation or/and an acknowledgement of past work.